Materia Revisionis Arisaemarum: III. taxonomic notes and five new taxa of the genus Arisaema (Araceae) from South China - Ma, Zhengxu (Phytotaxa, 2025)
In the course of systematic studies and fieldwork on the genus Arisaema in China between 2017 to 2024, five new species are being proposed and are herein described in detail, accompanied by photographs, diagnosed against allied species, and briefly analyzed the morphological variation patterns between related taxa. These newly proposed species are A. cordigerum, A. hui, A. mengii, A. pulchellum, and A. sceptrum. Arisaema thunbergii subsp. autumnale, native to Taiwan Island, is elevated to species status, while A. melanostomum has been synonymized to A. brevistipitatum, a previously overlooked name. Additionally, based on Engler’s unranked subgeneric division, Arisaema sect. Auriculata is proposed based on combined evidence. Furthermore, the identities of A. sinii and A. xuanweiense are re-examined, drawing on inspections of original materials. Lastly, the patterns of distribution observed and their biogeographical inferences are discussed for these newly discovered species and their closely related counterparts, emphasizing the rich diversity of Arisaema species in the subtropical South Chinese flora.